The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.30880/ijie.2020.12.05.018
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Surface Texturing in Internal Combustion Engine Piston Assembly

Abstract: This paper presents a brief review of surface texturing with a focus on piston assembly application. The paper begins with a general discussion on surface texturing and the manufacturing process of micro dimples. Further, it discusses the theory of hydrodynamic lift generation and the effect of parameters of micro dimples texture on the surface-to-surface friction. Finally, the effect of surface texturing on heat transfer is briefly discussed. In pursuits to improve internal combustion engine (ICE) efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 126 publications
(240 reference statements)
0
1
0
Order By: Relevance
“…The total area density of combined shapes studied is presented in table 3. It is suggested that area density is the most important parameter affecting the tribological performance of textured surface [42,43]. It should be in the optimum range to ensure beneficial effect of surface texture is obtained.…”
Section: Surface Texture Designmentioning
confidence: 99%
“…The total area density of combined shapes studied is presented in table 3. It is suggested that area density is the most important parameter affecting the tribological performance of textured surface [42,43]. It should be in the optimum range to ensure beneficial effect of surface texture is obtained.…”
Section: Surface Texture Designmentioning
confidence: 99%